Catalyzing Sustainable Finance: The Role of Decentralized Finance (DeFi) and Disruptive FinTech - Hadžić J. Jelena (International Journal of Innovative and Applied Finance, 2025)
The transition to a sustainable global economy requires significant redirection of financial flows, yet traditional financial mechanisms often face limitations in transparency, accessibility, and innovation. Decentralized Finance (DeFi) and other disruptive FinTech innovations offer novel pathways to mobilize capital for sustainable initiatives, but their effectiveness, risks, and governance implications remain underexplored. This research aims to investigate how DeFi protocols and other disruptive FinTechs (e.g., blockchain, AI) can enhance the efficiency, transparency, and accessibility of sustainable finance instruments. It also explores the key challenges and risks (e.g., regulatory, technological, ethical) associated with leveraging these technologies for sustainable transition. Case studies, quantitative analysis of transaction data, and conceptual modeling would be valuable. This research would contribute to finance and sustainability literature by exploring the synergistic potential of FinTech and sustainable finance, providing insights for financial institutions, investors, and policymakers on harnessing technological innovation for the green transition.